Penggunaan Trichoderma Sp. Untuk Mengendalikan Busuk Umbi Pada Bawang Merah (Allium Ascolanicum L.) - Dona Tiara; Ahmad Rafiqi Tantawi; Siti Mardiana (Universitas Medan Area, 2021)
The research objective was to determine the use of Trichoderma sp. to control shallots tuber (Allium ascalonicum L.). The research was conducted at Growth Center, Jl. Peradilan Tata Usaha Negara No. 1 Kenangan Baru, Percut Sei Tuan District, Deli Serdang Regency, 25 meters above sea level (asl). The design used was a factorial randomized block design (RBD) consisting of 2 factors, namely the factors of administration of Trichoderma sp. Consists of 5 levels, namely: T0: Control (without Trichoderma sp.), T1: 10 g Trichoderma sp./polybag, T2: 20 g Trichoderma sp./polybag, T3: 30 g Trichoderma sp./polybag, T4: 40 g Trichoderma sp./polybag. and time of giving Trichoderma sp. Consists 2 levels, namely: W1: Trichoderma sp. given 1 week before planting, and W2: 1 week after planting with 10 treatments combination. Observations included plant height (cm), number of leaves per clump (strands), number of tillers per clump (tuber), tuber wet weight per sample (g), tuber dry weight per sample (g), and the percentage of tuber rot attack. The results showed that: 1). The use of Trichoderma sp. with various doses (T0, T1, T2, T3, and T4) significant effect on plant height but no effect on observed other. While application time of Trichoderma sp. 1 week after planting (W2) showed a significant effect on plant height, number of leaves, number of tillers. also significantly affected wet weight, dry weight, and the percentage of tuber rot attack. 2). The combination of the two treatment factors had no significant effect on all observed parameters.